LEFT VENTRICULAR DIASTOLIC DYSFUNCTION AND ITS PATTERN IN TYPE 2 DIABETIC PATIENTS WITH AND WITHOUT MICROALBUMINURIA - Misbah Manzoor,; Babar, Bakht (Journal of Postgraduate Medical Institute, 2023)
Objective: To find out and compare left ventricular diastolic dysfunction and its pattern among patients with type-2 diabetes mellitus (T2DM) with and without micro-albuminuria. Methodology: This comparative cross section study was conducted in the outpatient department of Peshawar Institute of Cardiology from August 2021 to January 2022. A total of 228 T2DM normotensive patients, aged 30 to 65 years were enrolled and divided into two groups. Group-A contained 114 T2DM with no-albuminuria and Group-B had 114 T2DM micro-albuminuria patients. Socio-demographic, anthropometric, laboratory characteristics and echocardiographic parameters of all patients were noted. Qualitative variables were analyzed using chi-square test while quantitative variables were analyzed using t-test. P value <0.05 was considered statistically significant. Results: Out of a total of 228 patients, 122 (53.5%) were male. Overall, mean age was noted to be 49.18+8.8 years. In comparison to group-A, duration of diabetes was significantly more among patients of group-B (p<0.001). Renal functions were significantly preserved in Group-A in comparison to Group-B (p=0.003) as shown by eGFR. Left ventricular diastolic dysfunction was found to be 49.1% among patients of Group-A in comparison to 71.1% in Group-B and pattern of left ventricular diastolic dysfunction showed a significant difference between patients of both study groups (0.004). Conclusion: Left ventricular diastolic dysfunction was significantly high among T2DM patients with micro-albuminuria. Significant associations were found in terms altered left ventricular diastolic echocardiographic features among T2DM patients with micro-albuminuria.